Candles of Change: Nonviolent Resistance in Sudan (Journal of Political Science and International Relationship, 2024)
Overthrowing dictatorial regimes presents a formidable challenge, as these governments often maintain tight control over state mechanisms and media narratives; this paper explores the concept of nonviolent resistance, particularly within the context of the Sudanese revolution, utilising a qualitative research methodology and gathers qualitative data through interviews and focus groups with key participants in the Sudanese nonviolent movements. These include secondary data from online reports from civil society organisations of members of Resistance Committees and women activists. It also examines the tactics and strategies employed by nonviolent movements, including sit-ins, media campaigns, and the strategic use of the “butterfly effect,” demonstrating how small, coordinated actions can lead to significant societal change. The paper concludes with recommendations to strengthen civil society, enhance the capacity of Resistance Committees, and ensure women’s continued participation in the political process. These measures are essential for preserving the revolution’s achievements and supporting Sudan’s transition towards a more democratic and peaceful future.